Formação do professor de educação física para inclusão de alunos com deficiência - Fiorini, Maria Luiza Salzani [UNESP]; Manzini, Eduardo José [UNESP] (My University, 2014)
The paper aims to describe the steps undertaken in the development of a training program to prepare the physical education teacher to meet the demand of inclusion of students with disabilities. Seventeen physical education teachers who worked in public schools, from 1st to 5th grade, participated in the first step. The Data were collected through focus group. The analysis was performed in categories. Two teachers participated in Stage 2, which consists of 28 classes that there was a student with disabilities enrolled. The reports focus group identified eight different subcategories of difficulties: 1 ) Training , 2) Administrative-school issue ; 3 ) Student ; 4 ) Diagnosis ; 5 ) Family ; 6 ) Teaching resource ; 7 ) Strategies ; 8 ) Physical Education. The filming analysis enabled to identify difficulties and success situations of each teacher. The identification of the difficulties pointed out ways to prepare Physical Education teachers, and based on such difficulties actionsand contents that include a training program may be stipulated.

O texto objetiva descrever as etapas desenvolvidas na elaboração de um programa de formação para prover o professor de Educação Física para atender a demanda da inclusão de alunos com deficiência. Dezessete professores de Educação Física que atuavam em escolas municipais, do 1° ao 5° ano, participaram da primeira etapa. As informações foram coletadas por meio de Grupo Focal. A análise foi realizada em forma de categorias. Dois professores participaram da etapa 2, que consistiu na filmagem de 28 aulas em que havia um aluno com deficiência matriculado. Os relatos do grupo focal identificaram oito diferentes subcategorias de dificuldades: 1) Formação; 2) Questão Administrativo-escolar; 3) Aluno; 4) Diagnóstico; 5) Família; 6) Recurso pedagógico; 7) Estratégia; 8) Educação Física. A análise das filmagens possibilitou identificar dificuldades e situações de sucesso para cada um dos professores. A identificação das dificuldades indicou caminhos para prover os professores de Educação Física, na medida em que, a partir delas, poderão ser estipuladas ações e conteúdos que contemplem um programa de formação.

El artículo tiene por objetivo describir las etapas desarrolladas en la elaboración de un programa de capacitación para proporcionar soluciones al maestro de educación física para satisfacer la demanda de inclusión de los estudiantes con discapacidades. Diecisiete profesores de educación física que trabajan en escuelas públicas, de 1 º a 5 º grado, participaron en la primera etapa. Los datos fueron colectados por medio de grupo focal. El análisis se llevó a cabo en forma de categorías. Dos profesores participaron de la etapa 2, que consistió de la filmación de 28 lecciones en que había un estudiante con discapacidades matriculado. Los relatos del grupo focal identificó ocho diferentes subcategorías de dificultades: 1) la formación; 2 ) cuestiones administrativas de la escuela; 3) los estudiantes; 4) Diagnóstico; 5) Familia; 6) recursos pedagógicos; 7) Estrategia; y 8) Educación Física. El análisis de las filmaciones permitió la identificación de las dificultades y de las situaciones de éxito para cada profesor. La identificación de las dificultades señaló formas de proporcionar soluciones a los profesores de Educación Física, en la medida que, a partir de ellas, las acciones y los contenidos que contemplen un programa de formación podrán definirse.
Formación del profesorado de educación física para la inclusión de estudiantes con discapacidad
Physical education teacher training for inclusion of students with disabilities
Keywords: Educacao Especial; Formação de Professores; educação especial